High Energy Efficient Heterogeneous Networks: Cooperative and Cognitive Techniques - Heng Wang; Jiamo Jiang; Jian Li; Manzoor Ahmed; Mugen Peng (International Journal of Antennas and Propagation)
Heterogeneous network (HetNet) is considered as the main and eminent future communication technology, since it achieves high spectral efficiency per unit area and saves energy due to low transmission power. Mass deployment of small cells in cochannel mode increases overall system capacity, but it is also coupled with greater risk of cochannel interference. This paper overviews the interference model based on the Poisson point process (PPP) and analyzes the performance in terms of energy efficiency in multitier HetNet. As the promising solution for improving the performance of HetNet, both the cooperative communication and cognitive radio techniques to mitigate the interference in HetNet are surveyed. As one example of cooperative communication techniques, a hierarchical cooperation scheme on the spectrum allocation is presented and its energy efficiency performance is analyzed and evaluated. Meanwhile, the energy efficiency increases from the cognitive radio technique are demonstrated as well. The energy efficiency performance comparison between the presented cooperative communication and cognitive radio techniques is emphasized, which suggests that the cooperation communication technique is preferred to suppress the interference and increase the energy efficiency in HetNets.